Application of an Integrated Workmanship Benchmarking Framework to Building Failure in Developing Countries - Rakesh Sookoo; Joseph Iwaro; Abrahams Mwasha; Festus Olutoge; Kailas Sekhar Banerjee; Aaron Chadee; Lee Leon (Emerging Science Journal, 2025)
The construction industry is grappling with significant challenges related to measuring and assessing workmanship performance, which has led to instances of poor workmanship and even building failures. Traditional evaluation methods often fall short, underscoring the urgent need for a more integrated approach to performance assessment. Recent research focused on developing integrated performance assessment techniques and indicators for a comprehensive evaluation of building projects. Key factors contributing to poor workmanship include a lack of standardisation, inadequate assessment frameworks, and limited empirical knowledge. In response, this study proposes implementing an integrated benchmarking framework to evaluate workmanship performance more effectively, employing various data collection methods, including case studies, questionnaires, and checklist surveys, to assess workmanship performance across construction sites throughout the project lifecycle. The questionnaire targeted critical success factors, while checklist surveys identified key failure factors at various project stages. The findings reveal that this integrated benchmarking framework significantly reduces building defects and failures, enhancing overall workmanship quality within Trinidad and Tobago’s construction sector. Analysed projects demonstrated a notable decrease in defects and improvements in structural workmanship performance across all phases of the project. These results are expected to facilitate effective workmanship management in construction and promote the development of best practices in developing countries. This integrated benchmarking framework provides a comprehensive tool for evaluating workmanship performance across various building types, considering critical success and failure factors, project structures, and the organisations involved while offering continuous assessments throughout the lifecycle of building projects.